Tổng hợp và nghiên cứu tính chất phức chất dipivaloylmetanat của một số nguyên tố đất hiếm - Nguyệt, Triệu Thị; Hiền Lan, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The complexes of some rare earth elements with dipivaloylmethane (2,2,6,6-tetramethyl-3,5-heptandion) was synthesized and studied. The complexes was formed in mixture of ethanol - water solvent and their formula were Ln(DPM)3 (Ln: Sm, Gd, Er, Yb; DPM: dipivaloylmethanate). The synthesized complexes were studied by IR, thermal analysis and mass-spectroscopy methods. The obtained results showed that dipivaloylmethanates are monomes and thermostable. The separation of dipivaloylmethanates was supposed.